Outcome after neoadjuvant chemotherapy in Asian breast cancer patients. (20th December 2016) - Lim, Li Yan; Miao, Hui; Lim, Joline S. J.; Lee, Soo Chin; Bhoo‐Pathy, Nirmala; Yip, Cheng Har; Taib, Nur Aishah B. M.; Chan, Patrick; Tan, Ern Yu; Lim, Swee Ho; Lim, Geok Hoon; Woo, Evan; et al.
Abstract: We aim to identify clinicopathologic predictors for response to neoadjuvant chemotherapy and to evaluate the prognostic value of pathologic complete response (pCR) on survival in Asia. This study included 915 breast cancer patients who underwent neoadjuvant chemotherapy at five public hospitals in Singapore and Malaysia. pCR following neoadjuvant chemotherapy was defined as 1) no residual invasive tumor cells in the breast (ypT0/is) and 2) no residual invasive tumor cells in the breast and axillary lymph nodes (ypT0/is ypN0). Association between pCR and clinicopathologic characteristics and treatment were evaluated using chi‐square test and multivariable logistic regression. Kaplan–Meier analysis and log‐rank test, stratified by other prognostic factors, were conducted to compare overall survival between patients who achieved pCR and patients who did not. Overall, 4.4% of nonmetastatic patients received neoadjuvant chemotherapy. The median age of preoperatively treated patients was 50 years. pCR rates were 18.1% (pCR ypT0/is) and 14.4% (pCR ypT0/is ypN0), respectively. pCR rate was the highest among women who had higher grade, smaller size, estrogen receptor negative, human epidermal growth factor receptor 2‐positive disease or receiving taxane‐based neoadjuvant chemotherapy. Patients who achieved pCR had better overall survival than those who did not. In subgroup analysis, the survival advantage was only significant among women with estrogen receptor‐negative tumors. Patients with poor prognostic profile are more likely to achieve pCR and particularly when receiving taxane‐containing chemotherapy. pCR is a significant prognostic factor for overall survival especially in estrogen receptor‐negative breast cancers. Abstract : Most existing evidence on response to neoadjuvant chemotherapy are from western countries, where tumor characteristics are different from Asia. This study is one of the largest studies done in Asia to determine the demographic of breast cancer patients who underwent neoadjuvant chemotherapy, clinicopathologic predictors for response to treatment, their long‐term survival in an actual clinical practice setting, and the prognostic value of pathological complete response on overall survival in Asia.